INTERACTIVITY BETWEEN BODIES AND MILIEUS WITHIN TECHNO-AESTHETIC ART OBJECTS - Oliveira,Andreia Machado (2017)
Abstract Relations consist of processual interactivity between bodies and milieus which do not differentiate between the natural and the artificial, human and non-human. Our paper seeks to problematize the experience of the encounter with an artwork seen as a techno-aesthetic object constitutive of interactivity and addresses the idea of degrees of interactivity as produced with and within an artwork as an associated milieu. In this sense, we posit various degrees of interactivity in a relational experience: mixtures, attractions, embodiments and perceptions. Thus, interactive processes are driven by an ethics of the potential of bodies to act by what a body can do in its intensity, in the dynamics of degrees of interactivity in the experience. These ideas emerge from the philosophical writings of Baruch Spinoza, Gilbert Simondon and Gilles Deleuze and are applied to the field of art in order to allow an understanding of the relations between bodies and associated milieus.